Design and evaluation of 32P-labeled hydroxyapatite nanoparticles for bone tumor therapy - Dongliang Zhai; Yumei Wang; Songke Yu; Jiren Zhou; Jia Song; Shilei Hao; Xiaoliang Chen (Taylor & Francis Group, 2023)
AbstractThe clinical diagnosis and treatment of malignant bone tumors are still major clinical challenges due to their high incidence are difficulty. Targeted therapies have become a critical approach to treat bone tumors. In recent years, radiopharmaceuticals have been used widely and have shown potent and efficient results in treating bone tumors, among which 32P and the labeled radiopharmaceuticals play an essential role. In this study, the 32P-labeled hydroxyapatite (HA) was prepared through chemical synthesis (32P-Hap) and physical adsorption (32P-doped-Hap). The in vitro stability of 32P-labeled HA was analyzed to assess the superiority of the new-found chemical synthesis. The radiolabeling yield and stability of chemical synthesis (97.6 ± 0.5%) were significantly improved compared with physical adsorption (92.7 ± 0.4%). Furthermore, the CT results corroborate that 32P-Hap (100 μCi) +DOX group has the highest tumor suppression rate and can effectively reduce bone destruction. The results corroborate the effectiveness of the chemical synthesis and validate the application of 32P-Hap in bone tumors. Therefore, 32P-Hap (100 μCi) + DOX may be an effective strategy for bone metastasis treatments.